THE EFFECT OF JIGSAW TYPE OF COOPERATIVE LEARNING MODEL ON COGNITIVE LEARNING OUTCOMES OF CLASS VIII STUDENTS SMPN 40 PADANG - Frysia Premira Mondaylisa; Rani Oktavia; Yurnetti; Khairil Arif (Department of Science Education, 2026)
Learning in the 21st century requires students to be actively involved in learning activities. The 2013 curriculum also requires students to be actively involved during teaching and learning activities while the teacher acts as a facilitator. The 2013 curriculum also requires teachers to develop learning that integrates 4 important things, one of which is 21st century skills (4C skills). The character of the 4C skills is student centered (student centered learning), where students are required to be active in finding learning resources that can meet their learning needs. This study aims to determine the effect of the jigsaw cooperative model on the cognitive learning outcomes of class VIII students of SMPN 40 Padang. This research is a quasi-experimental research with a posttest only control group design. The results showed that the posttest average of the experimental class was 62.5 and that of the control class was 55.78. So it can be concluded that there is a significant influence of the jigsaw cooperative learning model on the cognitive learning outcomes of class VIII students of SMPN 40 Padang.